Phosphorus fractionation in volcanic lake sediments (Azores – Portugal) - Ribeiro, Daniel (2008)
The phosphorus distribution in volcanic sediments of three lakes that are under different anthropogenic pressures in São Miguel island (Azores – Portugal) was evaluated using a sequential extraction scheme. The P-fractionation scheme employs sequential extractions of sediment with NH4Cl, bicarbonate-dithionite (BD), NaOH (at room temperature), HCl and NaOH (at 85 °C) to obtain five P-fractions. The P-fractionation shows that in lakes with higher trophic status (Lake Furnas and Lake Sete Cidades), the NaOH extracted P is the dominant fraction, that contribute with more than 50% to total sedimentary phosphorus. The rank order of P-fractionation for these two lakes was NaOH > NaOH (85 °C) > HCl > BD > NH4Cl for Furnas lake and NaOH > HCl > NaOH (85 °C) > NH4Cl > BD for Sete Cidades lake. On the other hand, the trend of P contribution in the oligotrophic lake Fogo shows that the most inert P pools have the higher concentrations, with more than 50% of the P contribution from the last extraction step with NaOH at 85 °C. For this lake, the rank order of P-fractionation was NH4Cl > BD > NaOH > HCl > NaOH (85 °C). The Phosphorus Maximum Solubilization Potential (P-MSP) was also calculated and the results show that for the more bio-available P-fractions (first and second extraction step), the P-MSP values for Furnas and Sete Cidades lakes are sensibly higher than the results obtained in Fogo lake, an indication of the non-point diffuse load discharged in the first ones.